1989
DOI: 10.1091/mbc.1.1.13
|View full text |Cite
|
Sign up to set email alerts
|

1-O-alkyl-2-acetyl-sn-glycerol: a platelet-activating factor metabolite with biological activity in vascular smooth muscle cells.

Abstract: Platelet-activating factor (1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine; PAF) is a potent vasoactive ether lipid produced by activated blood cells and endothelial cells. Vascular smooth muscle cells partially convert exogenous PAF to 1-O-alkyl-2-acetyl-sn-glycerol (AAG), a biologically active diacylglycerol analogue. AAG is formed rapidly (less than 15 s) after exposure of the smooth muscle cells and does not appear to be a substrate for diacylglycerol kinase in these cells. Although most of the compound is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…Tbe l-alkyl-2-acetylglycerols, wbicb are neutral lipid products of PAF degradation by pbospbolipase C, also activate protein kinase C [3]. Alternatively, l-alkyl-2-acylglycerols, whicb can also be produced by PAF degradation (transacylation followed by phospbolipase C degradation), can inhibit protein kinase C activation [36].…”
Section: Paf-induced Intracellular Calcium Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tbe l-alkyl-2-acetylglycerols, wbicb are neutral lipid products of PAF degradation by pbospbolipase C, also activate protein kinase C [3]. Alternatively, l-alkyl-2-acylglycerols, whicb can also be produced by PAF degradation (transacylation followed by phospbolipase C degradation), can inhibit protein kinase C activation [36].…”
Section: Paf-induced Intracellular Calcium Mobilizationmentioning
confidence: 99%
“…JInresfDcmiato/105:816-823, 1995 P latelet-activating factor (l-alkyl-2-acetyl-glycero-3-phospliocholine; PAF) is a potent activator of many cell types including platelets, vascular endotlieliutn, neutrophils, mast cells, and tnonocytes [1,2], By actitig as both a cliemoattractant to recruit and as a stitnulus to activate granulocytic cells, PAF has profound proinBammatory cfFccts. In addition to the proinflammatory effects found with the stimulatioti of the above cell types, PAF bas mitogenic effects oti cultured smooth muscle and lymphoblastic cell lities [3][4][5]. Tbe majority of PAF actions are thovight to be exerted tlirougb ititeractioti witb a specific receptor, because radioligand binditig studies using [•'HJPAF have detnonstrated high-aftmity bitiding sites on PAFresponsive cells, and various structurally dissimilar PAF receptor antagonists can inbibit PAF effects [6], Tbe PAF receptor (PAF-R) Manuscript bas been cloned from guitiea pig lung [7J and bumati leukocytes [8].…”
mentioning
confidence: 99%
“…Platelet-activating factor (PAF) is a naturally occurring phospholipid (1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) cytokine and is well known as a potent mediator of allergic and inflammatory reactions (Prescott et al, 2000) and a potent regulator of proliferation and differentiation of immune cells (Stoll et al, 1991;Saito et al, 1992;Smith and Shearer, 1994). Recent studies suggest that the action of this potent lipid mediator is involved in a variety of physiological and pathological events in many cell types and tissues.…”
mentioning
confidence: 99%
“…Consistent with this, HAG prepared in vitro from phospholipase C-mediated cleavage of PAF stimulated a PKC-like activity in neuroblastoma cell homogenates in the presence of phosphatidylserine (another stimulatory lipid for PKC). It is not clear, however, which PKC isoforms were present in these samples, or perhaps more importantly, whether other kinases capable of phosphorylating the histone III substrate in the assay were present [ 84 ]. Surprisingly, this same group also found that pretreatment with HAG, DAG or OAG blocked phorbol ester binding to smooth muscle cells, suggesting that HAG effects may depend on additional, unidentified cellular factors [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps much of the seemingly discordant data surrounding HAG can be explained by a single HAG metabolite, HAGP ( Figure 1 g). In cancer cells, platelets and smooth muscle cells, HAG can be deacetylated to HG by AADACL1 [ 63 , 68 , 84 ]. In the absence of AADACL1 activity, however, HAG can be rapidly converted to its phosphorylated form, HAGP, by a DAG kinase-like enzyme (e.g., DGKα), in both human platelets and ovarian carcinoma cells [ 67 , 85 ].…”
Section: Introductionmentioning
confidence: 99%